Aspectos da distribuição de Pantopoda em Sargassum de Itanhaém e Ubatuba, São Paulo, Brasil - Varoli,Franci Mary Fantinato (1996)
Qualitative and quantitative aspects of the distribution of Pantopoda species living on Sargassum of Ubatuba and Itanhaém (northern and southern coast at São Paulo State, respectively) were studied. The results showed the occunence of nine Pantopoda species. The highest relative frequency was assigned to Tanystylum isahellae Marcus, 1940. In general the density of Pantopoda species was related to that of Hydrozoa covering Sargassum.